2014
DOI: 10.1007/s00198-014-2865-4
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens, the be-all and end-all of male hypogonadal bone loss?

Abstract: Gender is one of the strongest predictors of osteoporotic fracture risk, second only to ageing. A recent systematic review of worldwide epidemiology revealed that hip fracture incidence is about twofold lower in men compared to women, despite greater than tenfold variation between geographic regions [1]. This lower fracture incidence occurs despite persisting underdiagnosis and undertreatment of osteoporosis in men, which probably explains why hip fracture incidence may be decreasing in women but not men [2][3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Although non-aromatizable androgens can prevent bone resorption in rodent models, it remains controversial whether this is also the case in humans. Several experimental studies (Falahati-Nini et al, 2000;Idan et al, 2010;Laurent et al, 2015) have demonstrated that androgens were unable to prevent bone resorption in the face of estrogen deficiency and although they may selectively influence bone formation (Falahati-Nini et al, 2000), this has not been shown to translate into preservation of bone mass in aging men.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although non-aromatizable androgens can prevent bone resorption in rodent models, it remains controversial whether this is also the case in humans. Several experimental studies (Falahati-Nini et al, 2000;Idan et al, 2010;Laurent et al, 2015) have demonstrated that androgens were unable to prevent bone resorption in the face of estrogen deficiency and although they may selectively influence bone formation (Falahati-Nini et al, 2000), this has not been shown to translate into preservation of bone mass in aging men.…”
Section: Introductionmentioning
confidence: 97%
“…Because in aging, men maintain their sex steroid levels better than women, they do not experience the accelerated phase of bone loss observed after menopause in women. However a slow decline in the levels of bioavailable androgens and therefore also in E2, since androgens are the substrate for the aromatase enzyme and production of estrogens, could contribute to osteoporosis in aging men (Laurent et al, 2015). Although non-aromatizable androgens can prevent bone resorption in rodent models, it remains controversial whether this is also the case in humans.…”
Section: Introductionmentioning
confidence: 98%
“…Sex hormones and sex hormone-binding globulin has been shown to be correlated with loss of bone mineral density (BMD) ( Hsu et al, 2015 , Park et al, 2017 ), but not in all studies ( Paller et al, 2009 , Kuchuk et al, 2007 , Araujo et al, 2008 , Gennari et al, 2003 ). Previous studies revealed association between sex hormones and fracture risk ( Ohlsson et al, 2017 , Cauley et al, 2017 , Shahinian et al, 2005 ), particularly for estradiol ( Mellstrom et al, 2008 , Amin et al, 2006 , Garnero et al, 2000 , Laurent et al, 2015 , Cauley et al, 2010 , Khosla et al, 2008 , LeBlanc et al, 2009 ). Furthermore, previous research in men related testosterone (TT) and DHEAS to markers of bone turnover ( Kyvernitakis et al, 2013 ).…”
Section: Introductionmentioning
confidence: 94%
“…Whether inducible AR deletion at later age has any direct detrimental skeletal effects in skeletally mature mice, remains yet unanswered. This is an important topic for future research because a direct role of androgens in the development of osteoporosis in older men has not been confirmed Idan et al, 2010;Laurent et al, 2015). However, some epidemiological studies suggest that the combination of low serum E2 and T may be associated with higher fracture risk than low E2 alone (Amin et al, 2006;Woo et al, 2012).…”
Section: Role Of the Androgen Receptor (Ar)mentioning
confidence: 99%